Editorial: Transdiagnostic approaches to child and adolescent mental health—Integrating development, dimensions, and mechanisms - Alessio Bellato; Stephen P. Becker; Catharina A. Hartman; Henrik Larsson; James J. Li; Samantha J. Lynch; Giorgia Michelini (JCPP Advances, 2026)
Abstract Co‐occurrence of child and adolescent neurodevelopmental and mental health conditions is the rule rather than the exception, yet translating this insight into shared frameworks and clinical practice remains challenging. In this Editorial, we are pleased to introduce the 26 papers included in the 2026 Special Issue of JCPP Advances . This Special Issue aimed to advance our understanding of transdiagnostic mechanisms, dimensions, and practices in child and adolescent mental health, and includes original articles, reviews, commentaries, and an editorial perspective. Collectively, these articles illustrate three main ‘transdiagnostic’ conceptualisations; (i) mechanistic approaches identifying shared biological, cognitive, or affective processes across diagnostic boundaries; (ii) dimensional approaches mapping symptom covariance onto hierarchical structures such as the general ‘ p ’ factor and internalising, externalising, and neurodevelopmental spectra; and (iii) developmental, clinical‐staging approaches treating early, non‐specific features as precursors to a broad range of later outcomes. Methodologically, the current Special Issue highlights both the opportunities and limitations of large existing datasets, multi‐informant assessment, and neuroimaging and genomic approaches, while underscoring the persistent difficulty of modelling transdiagnostic dimensions developmentally. Importantly, while translation into routine clinical care remains limited, the field is now well positioned to test the clinical utility and effectiveness of transdiagnostic dimensional assessments and interventions in routine care.